2011
DOI: 10.4012/dmj.2010-111
|View full text |Cite
|
Sign up to set email alerts
|

Study on ceramic coating on the enamel surface using a carbon dioxide laser

Abstract: The aims of this study were to evaluate a new restorative method using a carbon dioxide laser (CO2-laser) and to evaluate the acid resistance of teeth. Experimental calcium phosphate glass (CPG) powder and two low melting point ceramics (Finesse and zirconium silicate) were fused to enamel surfaces using a CO2-laser at an irradiation intensity of 1.0 watt for 30 seconds with a beam size of 0.49 mm at the focal point. The treated teeth were observed with a scanning electron microscope, and the acid resistance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Moreover, substantial improvement in the acid resistance of the tooth structures could not be achieved by the fusion of the apatite powder only. Thus, considering the possibility of enhancing the acid resistance of the tooth structure by laser irradiation, we demonstrated the fusion of calcium phosphate glass to the enamel surface using a CO 2 laser in our previous studies [11][12][13][14]. This method enables the use of an active approach for the treatment of incipient carious lesions, such as pit and fissure sealants, in accordance with the recent minimal intervention concept in restorative dentistry.…”
Section: Effect Of Calcium Phosphate Glass On Dentinal Tubule Sealing After Irradiationmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, substantial improvement in the acid resistance of the tooth structures could not be achieved by the fusion of the apatite powder only. Thus, considering the possibility of enhancing the acid resistance of the tooth structure by laser irradiation, we demonstrated the fusion of calcium phosphate glass to the enamel surface using a CO 2 laser in our previous studies [11][12][13][14]. This method enables the use of an active approach for the treatment of incipient carious lesions, such as pit and fissure sealants, in accordance with the recent minimal intervention concept in restorative dentistry.…”
Section: Effect Of Calcium Phosphate Glass On Dentinal Tubule Sealing After Irradiationmentioning
confidence: 67%
“…The composition of calcium phosphate glass is similar to that of natural enamel (32% CaO, 11% SrO, 4% Al 2 O 3 , 52% P 2 O 5 , and 1% CeO 3 ). Previous studies have reported the fusion of the enamel with the calcium phosphate glass creating an indistinct margin in a gradient manner when the enamel was used as an adherend [11][12][13][14]. Therefore, calcium phosphate glass is considered to possess the ability to merge with the highly inorganic contents of the enamel.…”
Section: Discussionmentioning
confidence: 99%
“…laser de CO 2 ainda não foi avaliado na literatura para o tratamento superficial de porcelanas dentárias de forma a se produzir uma supefície mais lisa. O laser já foi sugerido para o tratamento de cerâmicas na odontologia, mas somente com propósito restaurador(Nihei et al, 2011) e, principalmente, adesivo(Kitayama et al, 2010;Paranhos et al, 2011). Um tratamento de superfície com o laser de CO 2 poderia, assim como o fez para a sinterização, reduzir o tempo necessário para o glazeamento da peça.…”
unclassified